In Situ and GRACE‐Based Groundwater Observations: Similarities, Discrepancies, and Evaluation in the High Plains Aquifer in Kansas. Issue 10 (19th October 2018) - Brookfield, A. E.; Hill, M. C.; Rodell, M.; Loomis, B. D.; Stotler, R. L.; Porter, M. E.; Bohling, G. C.
Abstract: Relating Gravity Recovery and Climate Experiment (GRACE)‐derived terrestrial water storage anomaly (aTWS) variations to in situ groundwater data is important to understanding GRACE data utility. Here GRACE‐derived annual changes in aTWS (ΔTWS) from National Aeronautics and Space Administration's Jet Propulsion Laboratory and Goddard Space Flight Center are compared to annual changes in saturated groundwater volumes (ΔGW) in the High Plains aquifer (HPA) and overlying alluvial aquifers in Kansas. Regression analysis suggests that trends in ΔTWS are strongly related to trends in ΔGWalluvial and weakly related to trends in ΔGWHPA, although the magnitude of ΔTWS is much larger than ΔGWalluvial and is similar to ΔGWHPA . Unlike alluvial aquifers, a thick vadose zone overlies the HPA. Estimates of changes in vadose zone water content (ΔVZ) using GRACE products are similar in magnitude to annual variations in North American Land Data Assimilation soil moisture data, suggesting an unexpected dominance of ΔVZ in ΔTWS despite significant groundwater depletion. Results demonstrate that water storage changes in shallow alluvial aquifers, the root zone, the deep vadose zone, and the HPA itself are all significant in the HPA region of Kansas. Consequently, GRACE observations cannot, alone, be taken to reflect variations in saturated zone groundwater storage in the HPA, or other large, heavily used aquifers subject to substantial groundwater depletion, when deep unsaturated zones exist. GRACE can best provide guidance on regional aquifer storage changes where water storage changes in the vadose zone and perched or adjacent aquifers are well constrained. Key Points: GRACE terrestrial water storage observations cannot, alone, be taken to reflect groundwater storage variations in the High Plains aquifer Water storage changes in shallow aquifers, the shallow and deep vadose zone, and the High Plains aquifer itself are all significant GRACE is best suited for estimating regional aquifer storage changes where vadose zone and shallow aquifer storage changes are well known